Management of maxillofacial trauma by dentists in Bengkulu Province, Indonesia: Penanganan trauma maksilofasial oleh dokter gigi di Provinsi Bengkulu, Indonesia - Adhe Ismunandar (Makassar Dental Journal PDGI Makassar, 2026)
Maxillofacial injuries are a group of injuries that can be life-threatening and interfere with vital functions. Proper and timely treatment is essential to prevent acute and long-term complications. Dentists play a central role in the initial assessment and treatment of these injuries. This study analyses how dentists in In-donesia manage maxillofacial injuries at various levels of healthcare facilities. A descriptive cross-sectional study was conducted using a structured question-naire administered to 30 dentists working in community health centres and hospitals of various types. Data were analysed using SPSS to obtain frequency distributions, percentages, and descriptive statistics. The findings show variations in clinical management related to the type of health facility and the clinical experience of the dentist. Common core management steps include airway assessment, bleeding control, and the application of advanced trauma life support (ATLS) (ABCDE) principles in the early phase of treatment. It was concluded that the management of maxillofacial trauma by dentists in Indonesia varies according to the work environment and professional experience. Continuing education and targeted training are needed to improve the competence of dentists in optimally handling these cases.